Hepatitis E: the West of Scotland experience. Issue 3 (August 2013) - Deshpande, A; Gunson, R; Bradley, A; Cameron, S
Background and aims: Hepatitis E virus is traditionally regarded as a virus of the developing world and is emerging as a leading cause of non-A/B/C hepatitis. We wished to investigate locally acquired transmission of hepatitis E in the West of Scotland and compare our use of traditional serology versus polymerase chain reaction since the introduction of polymerase chain reaction in 2007. Methods: Clinical details provided on specimens of blood positive for hepatitis E virus by serology or polymerase chain reaction were collated and analysed. Results: Since 2007, 30 samples were hepatitis E virus-positive by serology or polymerase chain reaction. Polymerase chain reaction positivity was generally associated with positive serology although four samples were polymerase chain reaction-negative and strongly positive by serology. Interestingly, one-quarter of cases were likely to represent endogenous transmission of the infection. Conclusions: Polymerase chain reaction is valuable in reliably diagnosing hepatitis E virus. However, serology is valuable for diagnosing resolved infection. There may be a high level of undiagnosed locally acquired hepatitis E virus in Scotland.